Recent applications in natural product synthesis of dihydro-furan and -pyran formation by ring-closing alkene metathesis - Hodgson, D; Jacques, R; Pal, R; Parker, N; Sear, C; Smith, P; Ribaucourt, A (Royal Society of Chemistry, 2016)
In the last two decades, alkene metathesis has risen in prominence to become a significant synthetic strategy for alkene formation. Many total syntheses of natural products have used this transformation. We review the use, from 2003 to 2015, of ring-closing alkene metathesis (RCM) for the generation of dihydro-furans or -pyrans in natural product synthesis. The strategies used to assemble the RCM precursors and the subsequent use of the newly formed unsaturation will also be highlighted and placed in context.